Cycling performance for storage and purification of lanthanum‐rich mischmetal alloy in the presence of hydrogen sulfide. Issue 9 (11th May 2021) - Miao, Shan; Eguchi, Akashi; Katayama, Noboru; Dowaki, Kiyoshi
Abstract: With the continuous expansion of the high‐purity hydrogen application range, the performance degradation of hydrogen storage alloy (HSA) caused by impurities has attracted widespread attention in producing pure hydrogen from biomass. In this study, the lanthanum‐rich mischmetal alloy's purification ability on hydrogen sulfide impurities and cycling performance were studied. The hydrogen with different concentrations of hydrogen sulfide was used to investigate the purification performance, which assumes the gas derived from biomass. Besides, a cycling experiment was designed to analyze cycling performance. The results show that the HSA could remove high concentrations of hydrogen sulfide entirely. It was also found that impurities of 1 ppm hydrogen sulfide had little effect on the HSA. With hydrogen sulfide concentrations of 100 ppm, the hydrogen storage capacity, absorption rate, and release rate were reduced, but they became a stable state from the second cycle. The performance degradation mechanism was analyzed by Energy Dispersive X‐Ray Spectroscopy (EDS) and X‐ray Photoelectron Spectroscopy (XPS​). Abstract : The purification ability of lanthanum‐rich mischmetal alloy on hydrogen sulfide impurities and cycling performance was studied. The results show that the hydrogen storage alloy could remove high concentrations of hydrogen sulfide entirely. It was also found that different concentrations of hydrogen sulfide will have different effects on hydrogen storage alloys.